Simplified 3D model for the uplift analysis of liquid storage tanks. (1st October 2019) - Colombo, J.I.; Almazán, J.L.
Highlights: A comprehensively analysis of the stress distribution on the tank wall for unanchored tanks was presented. A novel simplified 3D model for seismic analysis of unanchored tanks was developed. The hoop stress increases significantly when a considerable base uplift occurs. Both anchored and unanchored tanks may present a high compressive axial stress on the tank wall. Abstract: Vertical uplifting of the tank base is perhaps the most relevant characteristic of the seismic behaviour of unanchored cylindrical liquid storage tanks made of steel. When an unanchored tank is subjected to lateral loads due to the earthquake-induced hydrodynamic pressures, a portion of the base plate tends uplift locally. Analysis of the base plate uplifting of unanchored tanks implies many sources of nonlinear behaviour mechanisms such as the varying contact of the base plate with the foundation, large deflections, the material yielding and the plastic rotation of the base plate. This paper presents a comprehensive analysis of the partially uplifted base plate of two thin-walled cylindrical tanks (one slender and one broad). First, a nonlinear quasi-static cyclic analysis with a finite element model and a simplified model is carried out for each tank. Next, an efficient method for three-dimensional dynamic analysis is proposed and used in order to obtain the nonlinear time history response of each tank. The simplified non-linear model proposed in this paper was capable to provide a good estimation of both the rocking resistance of the liquid-loaded base plate and the stress distribution on the tank wall in contact with the foundation. A set of seven seismic ground motions was used for the time history analysis. Finally, the distribution of the tank wall stresses and the critical responses of the tanks are discussed. Both anchored and unanchored tanks may present a high compressive axial stress due to the seismic effect.